Aktualisasi 7 Surat Dalam Tradisi Mitoni - Muhammad Fuad Zain; Hasanudin Hasanudin (MAGHZA, 2018)
As the Quran is the most read holy book, efforts of grounding it is frequently undertaken by scholars in order to live Al-Qur’an in accordance with the term being relevant all time and place. The actualization of Al-Qur’an with local culture in mitoni which read seven letters in the Quran are al-Kaḥfi, Maryam, Yāsīn, Yūsuf, al-Raḥman, al-Wāqiah, and al-Mulk, in spite of various types of reading depending on the leader of the ceremony. A term referring to the realization of Quran in life is living Quran in which society places the Qur’an as being read and the highest guide for Moslems to attain a state of happiness in the world and the hereafter. The actualization of seven letters of the Quran is inseparable from the acculturation of local culture with Islamic values brought by Wali Songo especially from Tuban school which allowed and preserved the local culture with an Islamic nuance.